Two-trocar laparoscopic-assisted appendectomy versus conventional laparoscopic appendectomy in patients with acute appendicitis. - Konstadoulakis, Manousos M; Gomatos, Ilias P; Antonakis, Pantelis T; Manouras, Andreas; Albanopoulos, Konstantinos; Nikiteas, Nikolaos; Leandros, Emmanuel; Bramis, John (J Laparoendosc Adv Surg Tech A, 2006)
BACKGROUND: In order to reduce abdominal trauma and operative costs we have adopted a two-trocar laparoscopic-assisted appendectomy for patients with acute appendicitis. In the current study, the proposed technique is prospectively evaluated against conventional laparoscopic appendectomy with respect to feasibility, safety, and postoperative outcome. MATERIALS AND METHODS: Between July 2001 and July 2003, 83 consecutive patients were admitted with clinically diagnosed acute appendicitis and were randomly assigned to two-trocar laparoscopic-assisted appendectomy (n = 40, 48.2%) or conventional laparoscopic appendectomy (n = 43, 51.8%). RESULTS: Two-trocar laparoscopic-assisted appendectomy was successfully completed in 30 patients (80.1%). Four patients initially scheduled for two-trocar laparoscopic-assisted appendectomy (10.8%) were converted to laparotomy due to excessive body weight (BMI > or = 40), while an additional 5-mm infraumbilical trocar was inserted in another 3 patients (8.1%). The procedure was associated with decreased operative time and more rapid return to normal activity compared to laparoscopic appendectomy (P < 0.001 and P = 0.038, respectively). There was no statistically significant difference regarding the duration of hospitalization or the morbidity rate between the two groups. Conversion of the initial procedure was associated with increased wound infection rate and higher morbidity (P = 0.032 and P = 0.018, respectively). CONCLUSION: Two-trocar laparoscopic-assisted appendectomy represents a promising minimally invasive procedure for the treatment of acute appendicitis. It is fast and easy to perform, and it is expected to decrease the overall cost of laparoscopic appendectomy. Its only contraindication is excessive body weight; it remains to be evaluated in the setting of perforated appendicitis and retrocecally located appendices.
Keywords: Adolescent; Adult; Appendectomy; Appendicitis; Feasibility Studies; Female; Humans; Laparoscopes; Laparoscopy; Male; Middle Aged; Prospective Studies